Stannous chloride and stannous fluoride are inhibitors of matrix metalloproteinases. (November 2018) - Cvikl, Barbara; Lussi, Adrian; Carvalho, Thiago Saads; Moritz, Andreas; Gruber, Reinhard
Abstract: Objectives: Matrix metalloproteinases (MMPs) in dentin and saliva can degrade collagen. Divalent metals are known inhibitors of MMPs, but stannous – such as in the form of stannous chloride (SnCl2 ) or stannous fluoride (SnF2 ) – is yet to be tested for a possible inhibitory effect. In this study, we tested the inhibitory effect on the proteolytic activity of MMP-2 and MMP-9. Methods: Sodium chloride (NaCl), sodium fluoride (NaF), and chlorhexidine (CHX) were used as controls. Gelatin zymography was performed with recombinant human MMP-2 and MMP-9. SnCl2, SnF2, NaF, NaCl, and CHX were included either in the incubation buffer (M1) or added to the recombinant MMPs (M2) before the MMPs were analyzed using zymography. Furthermore, the effect of SnCl2, SnF2, and NaF on the enzymatic activity of MMP-2 and MMP-9 was measured in human dentin either before or after acid etching using 37%phosphoric acid. The effect of SnCl2, NaF, and CHX on the viability and of SnCl2 and NaF on the proliferation of human gingival fibroblasts and L929 mouse fibroblasts was also determined. Results: For M1, inhibitory concentrations (w/v%) of SnCl2 0.5% and 0.5%, SnF2 0.25% and 0.12%, NaF 0.12% and 0.5%, CHX 0.012% and 0.05%, were observed for MMP-2 and MMP-9, respectively. NaCl had no inhibitory effect. For M2, SnCl2 0.007% and 0.12%, and SnF2 0.03% and 0.5%, inhibited MMP-2 and MMP-9, respectively. NaF, NaCl and CHX had no effect. The enzymatic activity was slightly reduced when SnCl2 and NaF were applied on dentin before the acid attack. Regarding cell viability and proliferation of the cells after stimulation with the respective substances, NaF showed almost no effect, SnCl2 appeared to increase viability and proliferation of the cells, and CHX decreased the viability of cells. Conclusions: Stannous ions caused a direct inhibition of the matrix metalloproteinases, whereas F − only had an inhibitory effect when added to the zymography buffer. Clinical significance: Inhibition of MMPs using SnCl2 and SnF2 could play an important role in the prevention of dental erosion and caries. However, the clinical relevance of these findings needs to be proven.